The influence of trace elements on anaerobic digestion process = Wpływ pierwiastków śladowych na proces fermentacji metanowej - Myszograj, Sylwia; Stadnik, Artur; Płuciennik-Koropczuk, Ewelina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is the literature review on the importance of trace elements supplementation in the methane fermentation process. The production of biogas, including methane, as well as the efficiency of the process depend on the substrates to be fermented. Substances supplied with the substrate as well as products generated in the decomposition phases can inhibit the process. The factor limiting fermentation is the rate of enzymatic hydrolysis of substrates.
Keywords: anaerobic digestion; trace elements; process inhibition; biogas production; fermentacja metanowa; pierwiastki śladowe; inhibicja procesu; produkcja biogazu